Persistent angina pectoris in ischaemic cardiomyopathy: increased rehospitalization and major adverse cardiac events. (27th June 2014) - Mentz, Robert J.; Broderick, Samuel; Shaw, Linda K.; Chiswell, Karen; Fiuzat, Mona; O'Connor, Christopher M.
<x xml:space="preserve">Abstract</x> Aims The impact of refractory angina pectoris (AP) in patients with ischaemic cardiomyopathy (ICM) is unknown. We investigated the characteristics and outcomes of ICM patients with persistent AP following cardiac catheterization. Methods and results Patients who underwent coronary angiography at Duke from 2000 to 2009 with an EF <40% and ICM with persistent AP were compared with similar patients without persistent AP. Persistent AP was defined by patient report of ischaemic symptoms within 1 year of index catheterization. Time‐to‐event was examined using Kaplan–Meier or cumulative incidence and Cox proportional hazards modelling methods for death/myocardial infarction (MI)/revascularization [i.e. major adverse cardiac events (MACE)], death/MI, death, and cardiovascular death/hospitalization. Of 965 ICM patients, 298 (31%) had persistent AP. These patients were younger and had more previous revascularization than patients without persistent AP. Both groups had high use of aspirin, beta‐blockers, ACE inhibitors, and statins, but modest nitrate use. Over a median follow‐up of >5 years, patients with persistent AP had increased rates of MACE, and cardiovascular death/hospitalization compared with patients without persistent AP [5‐year cumulative event rates of 53% vs. 46% (P = 0.013) and 73% vs. 60% (P < 0.0001), respectively], but similar rates of death (P = 0.59) and death/MI (P = 0.50). After multivariable adjustment, persistent AP remained associated with increased MACE [hazard ratio (HR) 1.30; 95% confidence interval (CI) 1.08–1.57], and cardiovascular death/hospitalization (HR 1.36; 95% CI 1.14–1.62). Conclusion Persistent AP is common despite medical therapy in patients with ICM and is independently associated with increased long‐term MACE and rehospitalization. Future prospective studies of persistent AP in ICM patients are warranted.